Evaluation of the Antidiabetic Activity of Hydromethanolic Roots Extracts of Rumex abyssinicus Jacq: (Polygonaceae) in Swiss Albino Mice. (30th June 2022) - Yrga Adugna, Baye; Mequanint Adinew, Getinet; Ayalew Getahun, Kefyalew; Endale Gurmu, Abyot; Yirga Berhie, Alemshet; Awoke, Tewachew; Tessema Desta, Getaye
Abstract : Introduction . Diabetes Mellitus isa chronic metabolic disorder that required long-lasting treatment. In Ethiopian traditional medicine practices, abundant plants have been used for the treatment of diabetes mellitus for a long period. The root of Rumex abyssinicus is employed for the treatment of diabetes mellitus by Ethiopians. This study aimed to investigate the antidiabetic activity of the crude extract of Rumex abyssinicus root in Swiss albino mice. Methods . Cold maceration technique and hydro methanolic (80% methanol) solvent with occasionally shaking were employed during the crude extraction processes. To evaluate the antidiabetic activity of the crude extract, normoglycemic, glucose-loaded, and streptozotocin-induced diabetic models were used. In each model, the overnight fasted mice were randomly divided into five groups for normoglycemic and glucose-loaded models as a negative control, positive control, and three tested groups, whereas, in streptozotocin-induced diabetic models, the mice were grouped into six groups like one diabetic and one normal negative control groups, three diabetic tested groups, and one diabetic positive group. Each group comprised six mice. For all models, the tested groups received the crude extract at 100, 200, and 400 mg/kg doses, both diabetic and nondiabetic negative control groups received 10 ml/kg distilled water, and positive groups received 5 mg/kg glibenclamide. Results . The crude extract of the plant did not show any sign of toxicity up to 2000 mg/kg dose. In normoglycemic and oral glucose tolerance tests, the crude extract significantly (p < 0.01 ) reduced the blood glucose level at 200 and 400 mg/kg doses. In the streptozotocin-induced diabetes models, a significant effect was observed at all tested doses. Conclusion . The finding of this study revealed that the crude extract of the plant owned antidiabetic activity and supports the traditional use of Rumex abyssinicus root for the treatment of diabetes mellitus.